Adverse reactions following COVID-19 vaccination: An Ecuadorian experience. (December 2021) - Vanegas, Emanuel; Robles-Velasco, Karla; Osorio, María F.; Farfán Bajaña, María José; Sarfraz, Zouina; Sarfraz, Azza; Fernández Cadena, Juan Carlos; Andrade Molina, Derly Madeleiny; Panchana Lascano, Matias; Cherrez-Ojeda, Ivan
Abstract: Background: Limited large-scale studies have been conducted to investigate the adverse effects of COVID-19 vaccine in Latin America, particularly among the healthcare worker (HCW) population in Ecuador. The objective of this study was to assess a cohort of Ecuadorian healthcare workers for adverse reactions following vaccination with the Pfizer-BioNTech vaccine. Methods: We conducted an observational cross-sectional study to assess the potential adverse reactions to the Pfizer-BioNTech COVID-19 vaccine among a sample of healthcare workers (HCWs) in the city of Guayaquil, Ecuador, from March to May 2021. Results: The sample comprised 1291 patients, with a mean age of 39.3 years (SD, 13.5). In general, 79% (N = 1020) of participants presented an adverse effect of any type at first dose, while 75.1% (N = 969) did so at the second dose. Pain at the puncture site was the most common adverse effect overall after either the first (68.4%) and second (55.6%) dose. Regarding anaphylaxis, no participant developed the condition after the first dose, and only 0.2% (N = 2) developing it at the second dose. No fatalities were reported. Conclusion: Our findings suggest that adverse reactions following COVID-19 vaccination with the Pfizer-BioNTech vaccine are relatively common, albeit often mild and self-limited. Consistent with the literature there were few cases of anaphylaxis, and no deaths that could be attributed to the inoculation with the vaccine. We hope our findings can help to reassure the public that benefits of vaccination highly outweigh the risks and contribute to the effort of reducing vaccine hesitancy among those who are concerned about the safety and potential side effects. Highlights: - In general, reported adverse reactions were frequent among Ecuadorian healthcare workers, with pain at the puncture site the most common adverse effect. - Anaphylaxis following vaccination was extremely rare, and we found no fatalities related to the inoculation with either dose of the vaccine. - We hope our findings can help to reassure the public that benefits of vaccination highly outweigh the risks and contribute to the effort of reducing vaccine hesitancy among those who are concerned about the safety and potential side effects.